Impact of drying on pore structures in ettringite-rich cements. (June 2016) - Galan, I.; Beltagui, H.; García-Maté, M.; Glasser, F.P.; Imbabi, M.S.
Abstract: Drying techniques affect the properties of cement pastes to varying extents. The effect of different drying techniques on calcium sulfoaluminate-based (C$A) cements and their constituent phases is reported for a range of simulated and commercial C$A pastes which are benchmarked against an OPC paste. The recommended methodologies used to dry samples were identified from the literature and include D-drying and solvent exchange. These methods were used in conjunction with mercury intrusion porosimetry (MIP) and X-ray powder diffraction (XRPD) measurements to assess the changes in pore structure and the damage to crystalline phases, respectively. D-drying and isopropanol exchange are the most satisfactory and least damaging methods for drying C$A based pastes.